Development of Microlearning Teaching Materials Based on Local Culture of North Sumatera in The Subject of Elementary School Social Studies Education - Tambunan, Husna Parluhutan; Risma; Nasution, Yusra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study aims to: (1) describe the results of expert tests on the product of E-Book Based on Local North Sumatra Culture in the Elementary School Social Studies Education Course of PGSD Unimed, and (2) describe the usability of the development of Microlearning Teaching Materials Based on Local North Sumatra Culture in the Elementary School Social Studies Education Course of PGSD Unimed. The research method used is the research and development model (Research and Development/R&D) with the Van den Akker development model by developing Microlearning Teaching Materials for Elementary School Social Studies Education Based on Local North Sumatra Culture. The location of the research was carried out at the PGSD study program, FIP Unimed, located on Jl. Willem Iskandar / Pasar V, Medan. The population of this study was all PGSD Unimed students of the 2020 batch totaling 225 students consisting of 11 (AK) regular and extension classes. The sample of this study was carried out through class events and one class was selected, namely class B Regular 2020, totaling 40 students. The results of the study indicate that the Local Culture-Based E-Book of North Sumatra in the Elementary School Social Studies Education Course of PGSD that was developed has been validated by material and media experts. The average score obtained from the material experts in stage I was 71% with the criteria